Ab initio study of intrinsic point defects in PbTe: an insight into phase stability. (15th June 2015) - Bajaj, Saurabh; Pomrehn, Gregory S.; Doak, Jeff W.; Gierlotka, Wojciech; Wu, Hsin-jay; Chen, Sinn-Wen; Wolverton, Chris; Goddard, William A.; Jeffrey Snyder, G.
Abstract: The stability of intrinsic point defects in PbTe, one of the most widely studied and efficient thermoelectric material, is explored by means of Density Functional Theory (DFT). The origin of n - and p -type conductivity in PbTe is attributed to particular intrinsic charged defects by calculating their formation energies. These DFT calculated defect formation energies are then used in the Gibbs free energy description of this phase as part of the Pb-Te thermodynamic model built using the CALPHAD method, and in the resulting phase diagram it is found that its solubility lines and non-stoichiometric range agree very well with experimental data. Such an approach of using DFT in conjunction with CALPHAD for compound semiconductor phases that exhibit very small ranges of non-stoichiometry does not only make the process of calculating phase diagrams for such systems more physical, but is necessary and critical for the assessment of unknown phase diagrams.